1996
DOI: 10.1080/00071669608417922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fasting and refeeding on structures of the intestinal villi and epithelial cells in White Leghorn hens

Abstract: 1. The fine structural alterations of villi and epithelial cells in each part of the small intestine were investigated in layer-type hens fasted for 12 h to 20 d or refed for one day after each fasting period. 2. Within the first 24-h-fasting, villi of the duodenum showed a remarkable reduction in height and those of the jejunum revealed a gradual decrease; such a significant reduction of the villus height was not obtained in the ileum. After 36-h-fasting, villus height in each part gradually decreased with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 22 publications
4
71
1
3
Order By: Relevance
“…Esse efeito sobre o peso do intestino pode estar diretamente relacionado com o maior ou menor desenvolvimento morfológico da mucosa intestinal (Uni et al, 1998). É conhecido que o epitélio intestinal é particularmente afetado pela ausência de alimento, sendo a altura das vilosidades significativamente reduzida em aves expostas ao jejum (Yamauchi et al, 1996). Por outro lado, observaram que aves alimentadas aumentam a atividade enzimática na mucosa intestinal e correlacionaram esse fato ao peso do intestino e ao peso corporal.…”
Section: Idade (Dias)unclassified
“…Esse efeito sobre o peso do intestino pode estar diretamente relacionado com o maior ou menor desenvolvimento morfológico da mucosa intestinal (Uni et al, 1998). É conhecido que o epitélio intestinal é particularmente afetado pela ausência de alimento, sendo a altura das vilosidades significativamente reduzida em aves expostas ao jejum (Yamauchi et al, 1996). Por outro lado, observaram que aves alimentadas aumentam a atividade enzimática na mucosa intestinal e correlacionaram esse fato ao peso do intestino e ao peso corporal.…”
Section: Idade (Dias)unclassified
“…There are several possible reasons why ileal structure was unchanged in this experiment, including the resistance of the ileum to structural changes compared with other regions of the small intestine and possibly, the imposed high temperature stress was not severe enough so that plant extracts could exert a substantial effect. Yamauchi et al (1996) indicated that morphological changes in response to stressors occur more rapidly in the proximal two-thirds of the small intestine than in the ileum.…”
Section: Small Intestinal Morphologymentioning
confidence: 99%
“…The gastrointestinal tract is particularly responsive to stressors, which can cause a variety of changes including alteration of the normal protective microbiota (1) and decreased integrity of the intestinal epithelium (2). The nutritional stressors have deleterious effects on the absorptive epithelium of the intestine, resulting in reduction of villus height and crypt depth (3). Less is known about the effect of high environmental temperature on intestinal morphology.…”
Section: Introductionmentioning
confidence: 99%